Impact of health education on unmet needs of contraception in urban slums of Chandigarh, India - Kumar, Dinesh; Kalia, Meenu; Goel, N. K.; Sharma, M.K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Unmet need points to gap between some women reproductive intention and their contraceptive behavior. Unmet need for contraception is mainly attributed to lack of information, negative attitude, fear of adverse effects and social influences. The objective of this study was to investigate awareness and practice of contraceptive usage. And to estimate unmet need of contraception in the studied population and to identify the factors associated with it, and to evaluate impact of health education on unmet needs of contraception. Methods: A community-based longitudinal study was conducted in four randomly selected urban slum areas (colonies) of Chandigarh, India. A systematic two-stage random sample design was adopted. Results: Overall contraceptive awareness rates among women and men were increased from 84.1% to 96.3% and from 82.2% to 95.5% in post-interventional survey as compared to baseline survey. Contraceptive prevalence rates were found to be 57.3% and 65.5% respectively in pre interventional and post interventional surveys, against contraceptive awareness rates of 81.7% and 95.5% respectively, resulting in gaps between knowledge and practice to be unmet needs of contraception to the extents of 24.4% and 30.0% respectively in the two surveys. Conclusions: There is an urgent need of adopting some population specific integral strategies for changing social norms and attitudes of couples regarding reproductive issues, increase in contraceptives awareness as well as practice for reductions in unmet needs of contraception and unwanted/unplanned pregnancies.